Father Involvement as a Predictor of Self-Esteem at Puberty - Sandora Afita; Sarita Candra Merida; Tugimin Supriyadi (Inovan Publisher, 2026)
This study was motivated by the importance of self-esteem during puberty as a psychological aspect that plays a significant role in adolescents’ identity development. One factor presumed to influence self-esteem is father involvement in parenting. This study aimed to determine whether father involvement serves as a predictor of self-esteem during puberty. A quantitative research method with simple linear regression analysis was employed. The sample consisted of 103 adolescents in the pubertal stage who lived with or had a biological father and resided in Bekasi Regency. Participants were selected using a convenience sampling technique. The instruments used in this study were the Father Involvement Scale based on Lamb’s theory and the Self-Esteem Scale based on Mruk’s theory. The results showed that father involvement was a significant predictor of self-esteem during puberty (p < 0.001). The correlation coefficient (R) was 0.552, indicating a moderate positive relationship between father involvement and self-esteem. Furthermore, the coefficient of determination (R²) was 0.304, indicating that father involvement contributed 30.4% to the prediction of self-esteem, while the remaining 69.6% was influenced by other factors not examined in this study. These findings suggest that higher levels of perceived father involvement are associated with higher levels of self-esteem among adolescents.